Creative thinking and decision-making processes in EFL creative writing - Težak, Katja (ELOPE (Ljubljana), 2015)
Creativity has been discussed, observed and researched for hundreds of years in the fields of psychology and philosophy - from the ancient notion of the inspired genius, all the way to modern psychologists trying to define creativity and prove its effects. Creativity has recently become a buzzword in EFL teaching practices. We try to stimulate creative thinking in the classroom, but possibly forget to observe the processes within it. The article discusses definitions of creativity and presents a qualitative study on the decision-making processes within EFL creative writing and its connections to students' language learning. The qualitative study was conducted with two 3rd-year bachelor English students who were asked to plan and write a short story in English while doing a think-aloud protocol. The data were transcribed and coded in order to observe emerging categories in the students' reasoning for plot and language use decisions.
Keywords: kreativno mišljenje; kreativno pisanje; odločanje; poučevanje angleščine